FORGING PROCESS IN THREE TOOL FOLDING DIE (Metallurgy and Foundry Engineering, 2008)
The aim of the paper was presentation control lubrication influence on forging process and apply possibilities. Numerical modeling of the forging process in three tool folding die has been presented. Five different variants of lubrication method have been analysed in order to define lubrication influence on the filling process of the die impression. The results indicate full usefulness of presented lubrication method in planning forging technologies.